Sosialisasi Pentingnya Literasi dan Numerasi Digital Untuk Memilih Perguruan Tinggi Bagi Siswa - Ahmad Anis Abdullah; Muhammad Najib Mubarok; Robiatul Adawiya; Dyahsih Alin Sholihah; Rino Richardo; Esti Nawangsasi; Sri Wulandari Danoebroto; Abdul Tarom; Riyana Wulan Nur Hidayah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
On the other hand, openness of information increases the wealth of knowledge, but on the other hand, it makes us the object of information. The low literacy and numeracy skills of Indonesian human resources will be a big problem in information disclosure. Numeracy literacy skills play a very important role in helping students solve everyday problems. Literacy and numeracy are also very important in choosing a university, this is to avoid mistakes in choosing a major. This service activity aims to socialize the importance of digital literacy and numeracy in choosing a university for Madrasah Aliyah students. The methods used include planning, implementation and evaluation. Based on the results of the questionnaire, the results showed that students were able to utilize literacy and numeracy in reading digital information to choose a university